The Lattice Compatibility Theory LCT: Physical and Chemical Arguments from the Growth Behavior of Doped Compounds in terms of Bandgap Distortion and Magnetic Effects. (9th July 2013) - Boubaker, K.
Abstract : Physical and chemical arguments for the recently discussed materials-related Lattice Compatibility Theory are presented. The discussed arguments are based on some differences of Mn ions incorporation kinetics inside some compounds. These differences have been evaluated and quantified in terms of alteration of bandgap edges, magnetic patterns, and Faraday effect.